Abdominal tuberculosis in Indians: Still very pertinent. (May 2019) - Singh, Ayaskanta; Sahu, Manoj Kumar; Panigrahi, Manas; Behera, Manas Kumar; UthanSingh, Kanishka; Kar, Chinmayee; Narayan, Jimmy
Abstract: Introduction: Tuberculosis is a disease that has been affecting mankind since time immemorial and it still continues to be a global health concern. Objective of the study was to evaluate the burden, clinical profile, diagnosis and diagnostic difficulties and outcome of abdominal tuberculosis (AbT) in non human immunodeficiency virus (HIV) infected adults in the department of gastroenterology at a tertiary care hospital over a period of two years. Material & methods: It was an observational study and the study period was from January 2016 till January 2018. The patients who were sero positive for HIV virus were excluded from the study. Results: The number of patients hospitalized during the period of 2016–2018 with abdominal tuberculosis was 58. The burden of tuberculosis of indoor patients was 1.3 cases per every 100 patients admitted. Presenting complaint of most of these patients [61%] was abdominal pain. Constitutional symptoms like fever; weight loss and loss of appetite were present in only 40% of the patients. Ascites was the presenting sign in around 45% of the patients. Peritoneum was the most common site of involvement [27 out of 58]. Almost all of these patients [25 out of 27] presented with abdominal pain and abdominal distension. Intestine was the second most common site. Ileocaecal involvement was present in fourteen patients, while other areas of colon were involved in five patients. All the 58 patients were given anti tubercular therapy. There was complete resolution of tuberculosis in 91% of cases [53 out of 58 patients]. Six patients developed drug induced liver injury. Death occurred in two patients who had disseminated tuberculosis. Conclusion: Although the burden of the disease remains the same, availability of newer investigations has aided in its early diagnosis and availability of good drugs has reduced the mortality and morbidity.